The Communication Around Natural Risks in Mountain Regions: Analyzing the Effects of Belief and Social Differences - Mikaël Chambru; Jean-Philippe De Oliverira (Revue de Géographie Alpine)
This article analyzes communication concerning natural hazards in mountain regions. It draws on the actual policies of “preventive information” that involve researchers in the production of scientific expertise with a social and political aim. Communication is analyzed here through the prism of Information and Communication Sciences (ICS), rather than as a phenomenon of the dissemination of information requiring improvement. This study is based on an interdisciplinary “action-research” program (Geography and ICS) carried out in the Hautes-Alpes and Haute-Savoie regions over a period of three years. This article acts as an empirical and reflective object and provides a point of entry into the mountain terrain. The article analyzes contemporary changes in public communication aimed at changing individuals’ behavior relating to the environment in “at-risk” regions. Drawing on this experience, and on a critical approach in ICS, we seek to propose interdisciplinary dialogue on the dynamics of research and the production of knowledge about mountain regions.